2017
DOI: 10.12681/eh.11517
|View full text |Cite
|
Sign up to set email alerts
|

The tabanid fauna (Diptera: Tabanidae) of the Chirpan Eminences (Bulgaria)

Abstract: The study of the Chirpan Eminences tabanid fauna was completed by means of a route collection in 2008 and regular monthly collections from two localities during the active tabanid seasons in years 2010-2011. The research resulted in the capturing of 1202 tabanid specimens, 1124 of them were females and 78 males. Within this collected sample 24 species and subspecies from 8 genera were determined: Chrysops (2 species), Atylotus (1 species), Therioplectes (1 species and 1 subspecies), Hybomitra (3 species), Taba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 1 publication
0
27
0
Order By: Relevance
“…Silvius algirus Meigen, 1830 -TL, RW, BN; 0-300 m; 1; hom; Drensky 1929aKröber 1938;Chvála et al 1972;Ganeva , 2006. Silvius alpinus (Scopoli, 1763) [S. vituli Fabricius, 1805)] -B3, K9, S1, S23, TL, T31, O1, R1, R3, RW, BS; 0-2183 m; 1, 2, eanna;Nedelkov 1909Nedelkov , 1912Drensky 1929a;Kröber 1938;Drenowsky 1939;Leclercq 1957;Trifonov et al 1964;Chvála et al 1972;Ganeva 1993Ganeva , 1995aGaneva , 1996Ganeva , 1998Ganeva , 1999bGaneva , 2005aGaneva , 2006Ganeva , 2011Ganeva , 2017Ganeva & Penev 2002. ?…”
Section: Tabanidaementioning
confidence: 99%
See 3 more Smart Citations
“…Silvius algirus Meigen, 1830 -TL, RW, BN; 0-300 m; 1; hom; Drensky 1929aKröber 1938;Chvála et al 1972;Ganeva , 2006. Silvius alpinus (Scopoli, 1763) [S. vituli Fabricius, 1805)] -B3, K9, S1, S23, TL, T31, O1, R1, R3, RW, BS; 0-2183 m; 1, 2, eanna;Nedelkov 1909Nedelkov , 1912Drensky 1929a;Kröber 1938;Drenowsky 1939;Leclercq 1957;Trifonov et al 1964;Chvála et al 1972;Ganeva 1993Ganeva , 1995aGaneva , 1996Ganeva , 1998Ganeva , 1999bGaneva , 2005aGaneva , 2006Ganeva , 2011Ganeva , 2017Ganeva & Penev 2002. ?…”
Section: Tabanidaementioning
confidence: 99%
“…tricolor Zeller, 1842] -B3, S1, S23, TL, T1; 100-400 m; 1; nmi; Enderlein 1925;Drensky 1929b;Kröber 1938;Moucha. & Chvála 1964;Leclercq 1966;Chvála et al 1972;Ganeva 1993Ganeva , 1995aGaneva , 1995bGaneva , 1995cGaneva , 1996Ganeva , 1998Ganeva , 1999bGaneva , 2000Ganeva , 2008bGaneva , 2011Ganeva & Penev 2002;, 2019. Hybomitra aterrima (Meigen, 1820) [Sziladynus, Therioplectes, Tabanus] -E2, S211, TL, O5, O62, R1, R2, RW; 180-2654 m; 1, 2, cse, m;Nedelkov 1912;Drensky 1929aDrensky , 1931aDrensky , 1931bLeclercq 1957;Chvála et al 1972;Ganeva 1996Ganeva , 1998Ganeva , 2000Ganeva , 2006Ganeva , 2009bGaneva , 2017.…”
Section: Tabanidaementioning
confidence: 99%
See 2 more Smart Citations
“…This study was a part of the research, conducted on the fauna and activity of the horse flies of the Tabanidae family in the Chirpan Eminences. As a result of the study of the tabanid fauna composition in the Chirpan Eminences, (15) reported 28 species and subspecies belonging to 8 genera.…”
Section: Introductionmentioning
confidence: 99%